Challenges in Securities Markets Regulation: Investor Protection and Corporate Governance - Paul Tucker; Michael Haliassos; Theodor Kockelkoren; Juan Carlos Ureta; José Manuel González-Páramo; Lori J. Schock; Colin Mayer; Eddy Wymeersch (SUERF - The European Money and Finance Forum, 2015)
On November 14th, 2014, SUERF – The European Money and Finance Forum – and CNMV, Comisión Nacional del Mercado de Valores – the Spanish Authority for supervision of securities markets – jointly organized a conference in Madrid: Challenges in Securities Markets Regulation: Investor Protection and Corporate Governance. The conference was part of the activities arranged to celebrate the 25th anniversary of the creation of the CNMV. The present SUERF Study includes a selection of papers based on the authors' contributions to the Madrid conference.
Keywords: D14; D18; D82; D83; G11; G14; G18; G21; G28; G32; K22; 330; Wertpapierhandel; Finanzmarktregulierung; Anlegerschutz; Corporate Governance; Welt